Mechanical and Metabolic Power in Accelerated Running-PART I: the 100-m dash - di Prampero, O. E.; Osgnach, C.; Morin, J.-B.; Zamparo, P.; Pavei, G. (European Journal of Applied Physiology, 2023)
Purpose Acceleration phases require additional mechanical and metabolic power, over and above that for running at constant velocity. The present study is devoted to a paradigmatic example: the 100-m dash, in which case the forward acceleration is very high initially and decreases progressively to become negligible during the central and final phases.